FSI analysis of artery suffering atherosclerosis - Chee, Kwok Chien (2011)
From the statistics of international death rates, United States shows 169.4 per 100,000 of population death in year 2005 because of coronary heart disease (CHD). An atheroma is an accumulation and swelling an artery walls that made up of (mostly) macrophage cells, or debris, that contain lipids (cholesterol and fatty acids), calcium and a variable amount of fibrous connective tissue. It results the artery wall thickens and hardens. This is called as atherosclerosis or “hardening of the arteries“. Thus, will resulting in a heart attact and ensuing debility. In this project, a Fluid – Structure Interaction analysis is done on a blood flow in an artery which suffers atherosclerosis disease. The most often atherosclerotic plaque accumulate is at the abdominnal aorta. This analysis is done on a simplified model of abdominal aorta. The conditions to be analyze is regarding to the size and the stiffness of the atheroma. The software tools that using in this research is the ANSYS Workbench, with the coupling of ANSYS and CFX analysis. The output result of structural analysis of the abdominal aorta shows that the abdominal with the size of 15% atheroma shows the highest value of the Maximum Total Mesh Displacement and Von Mises Stress. While the result of fluid analysis of the blood flow in abdominal aorta shows that the increases of size and stiffness of atherma will increases the absolute gradient for the pressure and velocity of blood flow at the point 3 in analysis. However, the increases of absolute gradient of velocity and pressure of blood flow for the increases of atheroma stiffness is lower than the increases of absolute gradient of velocity and pressure of blood flow for the increases of atheroma size. Thus, the visualization of the interaction between blood flow and artery wall in the vicinity of atheroma will help medical researchers and doctor understand atherosclerosis better.